Pengaruh Aktivitas Belajar terhadap Hasil Belajar IPA Siswa di Sekolah Dasar Negeri Se-Gugus Ahmad Dahlan Kecamatan Sruweng Kabupaten Kebumen - Darsono Darsono (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
This study aims to reveal the effect of learning activities on students' science learning outcomes at SD N in the Ahmad Dahlan cluster, Sruweng sub-district, Kebumen regency. This research is a quantitative research. The population in this study were all students at SD N in the Ahmad Dahlan cluster, Sruweng sub-district, while the sample in this study were fifth grade students in SD N in the cluster Ahmad Dahlan, Sruweng sub-district, totaling 89 students. Data collection used a questionnaire, and data analysis used a simple regression analysis technique. This study resulted in the conclusion that learning activities have a positive and significant influence on students' science learning outcomes in public elementary schools in the Ahmad Dahlan cluster, Sruweng sub-district, Kebumen regency. This is evident from the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (r2) = 0.385 or a contribution of 38.5%.